Adaptive Livestock Innovation for Global Food Security: Resilience Strategies for Animal Food Production in an Era of Crisis - Feri Hardiyanto (Politeknik Siber Cerdika Internasional, 2025)
The global food crisis, intensified by climate change, geopolitical conflicts, and unequal food distribution, necessitates innovative approaches in animal food production systems. Technology-based adaptive livestock farming offers a strategic solution to enhance food security and ensure sustainable production amid global uncertainties. This study aims to develop an integrative adaptive livestock innovation strategy to increase animal food output and bolster global food security, especially in tropical and crisis-prone countries. Using an exploratory qualitative approach, the research conducted case studies in Indonesia, Kenya, and Brazil. Data collection involved in-depth interviews, field observations, questionnaires, and policy document analysis. Data analysis was performed thematically and with descriptive statistics, employing triangulation to validate findings. The results indicate that adaptive livestock systems—such as smart feeding, IoT-based monitoring, and local feed substitution—can boost livestock productivity by an average of 25–33%. Farms implementing these innovations demonstrated greater resilience to feed shortages and climate disruptions. Most respondents affirmed that innovation significantly improves the efficiency and sustainability of livestock businesses. This study’s novelty lies in its integrative approach, combining multiple technologies and policies across diverse countries to formulate a comprehensive strategy for resilient and sustainable animal husbandry. Adaptive livestock farming thus plays a vital role in addressing the global food crisis, with collaborative strategies integrating technology, policy, and farmer empowerment being essential for transforming livestock systems towards food security